2017
DOI: 10.1038/eye.2017.161
|View full text |Cite
|
Sign up to set email alerts
|

The application of an acellular dermal allograft (AlloDerm) for patients with insufficient conjunctiva during evisceration and implantation surgery

Abstract: PurposeTo describe the use of an acellular dermal allograft (AlloDerm) for patients with insufficient conjunctiva during evisceration and implantation surgery.Patients and methodsThe medical records of six patients with insufficient conjunctiva during evisceration surgery were reviewed. It was not possible to close the Tenon's capsule and conjunctiva without wound tension in these patients, so AlloDerm was placed over the sclera, and the edges were sutured with adjacent conjunctiva without tension. The size of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Previous studies have described successful use of allografts to prevent or repair exposed orbital implants. 14,15 In our case series we have found Tutoplast ® patch graft to be an acceptable material for exposed orbital implants providing excellent coverage of the implant and acting as a scaffold for epithelialisation. The Tutoplast ® process is a scientific method of virally inactivating, preserving and sterilising human tissue, which can be safely used as an allograft.…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies have described successful use of allografts to prevent or repair exposed orbital implants. 14,15 In our case series we have found Tutoplast ® patch graft to be an acceptable material for exposed orbital implants providing excellent coverage of the implant and acting as a scaffold for epithelialisation. The Tutoplast ® process is a scientific method of virally inactivating, preserving and sterilising human tissue, which can be safely used as an allograft.…”
Section: Discussionmentioning
confidence: 76%
“…In clinical scenarios, tarsal plate defects are often accompanied by conjunctival deficiency, and reconstruction of tarsal plate defects with acellular dermal matrix grafts often requires a local conjunctival flap or other autografts for reconstruction of the inner layer lining 11,99,100 . For patients with insufficient conjunctival tissue, an acellular dermal matrix graft can be transplanted to the defective posterior lamella with the dermal surface oriented toward the wound bed and the basement membrane facing the ocular surface, which allows full conjunctival epithelialization over the graft surface within 3–6 weeks postoperatively 101 . However, the main drawback limiting the widespread use of ADM grafts is graft contraction and resorption, especially for grafts originating from humans 102 .…”
Section: Acellular Approachesmentioning
confidence: 99%
“…Nadal et al 93 reported excellent outcomes in evisceration with autogenous scleral grafting and ceramic implantation. Park et al 94 described the use of an acellular dermal allograft in patients with insufficient conjunctiva to cover the sclera and implant in a tension-free manner.…”
Section: Surgical Technique Of Eviscerationmentioning
confidence: 99%